Preparation and application of low-defect metal appearance effect spraying-free material
By mixing the flow mark and welding wire masterbatch with metal spray-free material similar to the flow mark and welding wire, the flow mark and welding mark problems caused by the flip of metal pigments during injection molding in the prior art are solved, and the appearance effect of low defect metal is achieved, and the product quality and aesthetics are improved.
Patent Information
- Application Number
- CN202411674276.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-04
AI Technical Summary
In the existing spray-free metal effect coloring technology, metal pigments such as metal sheets, pearlescent powder or mica powder are easily flipped during injection molding, resulting in flow marks and welding marks, affecting product quality and customer needs.
By preparing flow-form masterbatches with similar colors as flow marks and welded wires, and mixing them with metal-effect spray-free materials to form low-defect metal-appearance spray-free materials.
It effectively reduces the appearance of flow marks and welding marks, improves the quality and aesthetics of the product, and meets customers' needs for high-quality spray-free materials.
Smart Images

Figure BDA0005146647950000021 
Figure BDA0005146647950000031 
Figure BDA0005146647950000032
Abstract
Description
Technical Field
[0001] The invention belongs to the field of spray-free plastics and relates to the preparation and application of a spray-free material with a low-defect metallic appearance. Background Art
[0002] Spray-free materials do not require spraying, and a single injection molding process can produce a variety of differentiated appearance effects to meet the personalized requirements of different application scenarios. In the field of plastic product processing, the use of metal spray-free materials not only has a metallic texture in appearance, but the materials are also more environmentally friendly, eliminating the spraying process, while reducing multiple processes such as transportation and transit, reducing processing costs. The spray-free metal effect appearance is favored by consumers and is increasingly used in home appliances, automobiles and other fields. It is a product with great potential. However, the current mainstream spray-free metal effect coloring technology still has shortcomings: because metal pigments such as metal flakes, pearlescent powder or mica powder are flaky, they are easy to flip over during the injection molding process, which can easily produce flow marks and weld marks, affecting the quality of the product and failing to meet the usage requirements of many customers. Weld marks and flow marks are technical difficulties in the application of spray-free materials, which seriously affect the use and popularization of spray-free materials. Summary of the Invention
[0003] In view of the above problems, the present invention aims to address the problems existing in the prior art and provide a method for preparing and applying a spray-free material with a low-defect metallic appearance. The spray-free material with a low-defect metallic appearance provided by the present invention can be made of polyacrylonitrile-butadiene-styrene copolymer (ABS), or polycarbonate resin (PC) / polyacrylonitrile-butadiene-styrene copolymer (ABS), or polycarbonate resin (PC).
[0004] The object of the present invention is achieved through the following technical solutions:
[0005] <First Aspect>
[0006] The present invention provides a method for preparing a spray-free material with a low-defect metallic appearance, the method comprising the following steps:
[0007] S1. Injection mold the metal effect spray-free material into a plate and observe the flow marks and weld line colors;
[0008] S2. preparing a flow mark effect masterbatch with a color similar to that of the flow mark and weld line;
[0009] S3. Mixing the flow effect masterbatch with the metallic effect spray-free material to obtain the low-defect metallic appearance effect spray-free material.
[0010] As one embodiment of the present invention, the base material of the metallic effect spray-free coating material is at least one of a polycarbonate resin and a polyacrylonitrile-butadiene-styrene copolymer. In some embodiments, the polyacrylonitrile-butadiene-styrene copolymer has a polybutadiene content of 10-20% and a melt index of 20-60 g / 10 min when tested at 220°C / 10 kg. The polycarbonate resin has a melt index of 10-60 g / 10 min when tested at 300°C / 1.2 kg.
[0011] As an embodiment of the present invention, the base material of the flow effect masterbatch is polyethylene terephthalate resin. In some embodiments, the intrinsic viscosity of the polyethylene terephthalate resin is 0.6 to 1.2 dl / g.
[0012] As an embodiment of the present invention, the addition amount of the rhytide effect masterbatch in the low-defect metal appearance spray-free material is 0.5 to 5 wt.%.
[0013] As one embodiment of the present invention, the flow effect masterbatch is prepared by uniformly mixing the following raw materials in parts by weight and then melt-extruding and granulating them:
[0014] 100 parts of polyethylene terephthalate resin,
[0015]
[0016] In some embodiments, the intrinsic viscosity of the polyethylene terephthalate resin in the flow effect masterbatch is 0.6 to 1.2 dl / g. The compatibilizer is a long-chain polyolefin grafted with maleic anhydride or glycidyl methacrylate. Antioxidant #1 is antioxidant 1010 or antioxidant 1076; antioxidant #2 is antioxidant 168 or antioxidant 300. The lubricant is one or two of pentaerythritol tetrastearate, ethylene bisstearamide, and a stearate salt. The weathering agent is at least one of a benzotriazole and a hindered amine.
[0017] In one embodiment of the present invention, to prepare a flow effect masterbatch having a color similar to that of flow marks and weld lines, the raw materials are mixed and then added to a twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are set at 200-220°C, 210-230°C, 220-240°C, 230-250°C, and 240-260°C, respectively, and the twin-screw speed is 400-600 rpm. The masterbatch having a flow effect color similar to that of the flow marks and weld lines is prepared by melt extrusion and granulation.
[0018] As an embodiment of the present invention, the metal effect spray-free material is prepared by the following method S11:
[0019] Method S11 includes the following steps:
[0020] S11-1 Preparation:
[0021] 0 to 100 parts of polyacrylonitrile-butadiene-styrene copolymer,
[0022] Polycarbonate resin 0-70 parts,
[0023]
[0024] Wherein, polyacrylonitrile-butadiene-styrene copolymer and polycarbonate resin are not both 0;
[0025] S11-2, mixing the raw materials in step S1-1 uniformly and subjecting them to melt extrusion and granulation to obtain the metal effect spray-free material.
[0026] As one embodiment of the present invention, in step S11-2, the raw materials from step S11-1 are mixed and then added to a twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are 190-230°C, 200-240°C, 210-250°C, 220-260°C, and 230-270°C, respectively, and the twin-screw speed is 400-600 rpm. A metallic-effect spray-free material is prepared by melt extrusion and granulation.
[0027] As an embodiment of the present invention, the metal effect spray-free material is prepared by the following method S12:
[0028] Method S12 includes the following steps:
[0029] S12-1. Preparation of natural color materials
[0030] The following raw materials in parts by weight were mixed and then melt-extruded and granulated to prepare the natural color material:
[0031] 0 to 100 parts of polyacrylonitrile-butadiene-styrene copolymer,
[0032]
[0033] Wherein, polyacrylonitrile-butadiene-styrene copolymer and polycarbonate resin are not both 0;
[0034] S12-2. Preparation of Metallic Effect Rhythm Masterbatch:
[0035] The following raw materials in parts by weight were mixed evenly and then melt-extruded and granulated to prepare metallic effect rhyolite masterbatch:
[0036] 100 parts of polyethylene terephthalate resin,
[0037]
[0038] S12-3. The natural color material obtained in S12-1 and the metallic effect rhyolite masterbatch obtained in S12-2 are melt-extruded and granulated to obtain the metallic effect spray-free material.
[0039] As an embodiment of the present invention, in methods S11 and S12, the polyacrylonitrile-butadiene-styrene copolymer has a polybutadiene content of 10-20% and a melt index of 20-60 g / 10 min at 220°C*10 kg. The polycarbonate resin has a melt index of 10-60 g / 10 min at 300°C*1.2 kg. The compatibilizer is a long-chain polyolefin grafted with maleic anhydride or glycidyl methacrylate. The antioxidant #1 is antioxidant 1010 or antioxidant 1076. The antioxidant #2 is antioxidant 168 or antioxidant 300. The lubricant is one or two of pentaerythritol tetrastearate, ethylene bisstearamide, and stearate. The weathering agent is at least one of benzotriazoles and hindered amines. The metallic color powder is made of aluminum and has a particle size of 1-100 μm.
[0040] Method S12 was used to prepare a metallic-effect spray-free material. The difference between a metallic-effect flow-effect masterbatch and a flow-effect masterbatch with a color similar to that of flow marks and weld lines lies in their color. Specifically, based on the formula of the metallic-effect flow-effect masterbatch, by removing the metallic toner and adjusting the toner color, a flow-effect masterbatch with a color similar to that of flow marks and weld lines was obtained.
[0041] As an embodiment of the present invention, in the metallic effect rhyolite masterbatch of method S12, the intrinsic viscosity of the polyethylene terephthalate resin is 0.6-1.2 dl / g.
[0042] As an embodiment of the present invention, in step S12-1, when preparing the natural color material, the raw materials are mixed and then added to the twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are 190-230°C, 200-240°C, 210-250°C, 220-260°C, and 230-270°C, respectively, and the twin-screw speed is 400-600r / min.
[0043] In one embodiment of the present invention, in step S12-2, when preparing a metallic effect flow masterbatch, the raw materials are mixed and then added to a twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are 200-220°C, 210-230°C, 220-240°C, 230-250°C, and 240-260°C, respectively, and the twin-screw speed is 400-600 rpm. The metallic effect flow masterbatch is obtained by melt extrusion and granulation.
[0044] As an embodiment of the present invention, in step S12-3, the amount of the metallic effect rhyolite masterbatch added to the metallic effect spray-free material is 5 wt.% to 50 wt.%.
[0045] As one embodiment of the present invention, the flame retardant masterbatch is prepared by uniformly mixing the following raw materials in parts by weight and then melt-extruding and granulating them:
[0046]
[0047] As one embodiment of the present invention, when preparing the flame retardant masterbatch, the raw materials are mixed and then added to the twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are 210-230°C, 220-240°C, 230-250°C, 240-260°C, and 250-270°C, respectively, and the twin-screw speed is 400-600r / min.
[0048] As an embodiment of the present invention, the flame retardant is at least one of triphenyl phosphate, tricresyl phosphate, resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), and bisphenol A diphosphate.
[0049] <Second Aspect>
[0050] The present invention also provides a spray-free flow pattern effect plastic product, which is prepared by injection molding the spray-free material with low-defect metal appearance effect obtained by the above method.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The material obtained by the method of the present invention can be made into a spray-free flow pattern effect plastic product with both mechanical properties and aesthetics after injection molding. DETAILED DESCRIPTION
[0053] The present invention will be described in detail below with reference to the examples. The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that those skilled in the art may make several adjustments and improvements without departing from the scope of the present invention. These all fall within the scope of protection of the present invention.
[0054] Example 1
[0055] This embodiment provides a method for preparing a low-defect, metallic-looking, spray-free ABS material and its preparation method. The preparation process includes the following steps:
[0056] (1) Preparation of metal effect spray-free ABS material
[0057]
[0058] Polyacrylonitrile-butadiene-styrene copolymer (ABS), a compatibilizer, antioxidant #1, antioxidant #2, a lubricant, a weathering agent, a metallic toner, and toner #1 were mixed uniformly by weight and added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 190°C, 200°C, 210°C, 220°C, and 230°C, respectively, and the twin-screw speed was 500 r / min. The ABS metallic-effect, spray-free material was prepared by melt extrusion and granulation.
[0059] The ABS metal-effect spray-free material prepared in step (1) was injection molded into a plate, and the flow marks and weld line colors of the metal plate were observed.
[0060] (2) Preparation of flow effect masterbatch with similar color to flow marks and weld lines
[0061]
[0062] Polyethylene terephthalate resin (PET), compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, and color powder #2 were mixed by weight and then added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 210°C, 220°C, 230°C, 240°C, and 250°C, respectively, and the twin-screw speed was 500 r / min. A flow-marking masterbatch with a color similar to that of flow marks and weld lines was prepared through melt extrusion and granulation.
[0063] (3) The flow effect masterbatch prepared in step (2) having a color similar to that of flow marks and weld lines is added at a ratio of 1 wt.% and mechanically mixed with the ABS metal effect spray-free material to obtain a low-defect metal appearance spray-free ABS material.
[0064] The polyacrylonitrile-butadiene-styrene copolymer (ABS) has a polybutadiene content of 20% and a melt index of 30 g / 10 min at 220°C / 10 kg. The compatibilizer is ethylene-ethyl acrylate grafted maleic anhydride. The polyethylene terephthalate resin (PET) has an intrinsic viscosity of 0.8 dl / g. Antioxidant 1# is antioxidant 1010. Antioxidant 2# is antioxidant 168. The lubricant is ethylene bisstearamide. The weathering agent is UV-P. The metallic toner is made of aluminum with a particle size of 10 μm. Toner 1# is a conventional pigment blend of titanium dioxide, titanium yellow, and iron oxide red in a mass ratio of 1:0.1:0.1. Toner 2# is a conventional pigment blend of carbon black, titanium dioxide, titanium yellow, and iron oxide red in a mass ratio of 2:0.5:0.1:0.05.
[0065] Example 2
[0066] This embodiment provides a method for preparing a low-defect, metallic-looking, spray-free ABS material and its preparation method. The preparation process includes the following steps:
[0067] (1) Preparation of natural color ABS material
[0068]
[0069] Polyacrylonitrile-butadiene-styrene copolymer (ABS), a compatibilizer, antioxidant #1, antioxidant #2, a lubricant, and a weathering agent were mixed uniformly by weight and added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 190°C, 200°C, 210°C, 220°C, and 230°C, respectively, and the twin-screw speed was 500 r / min. Natural-color ABS material was prepared by melt extrusion and granulation.
[0070] (2) Preparation of metallic effect rhyolite masterbatch
[0071]
[0072] Polyethylene terephthalate resin (PET), compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, metallic colorant, and colorant #1 were mixed uniformly by weight and added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 210°C, 220°C, 230°C, 240°C, and 250°C, respectively, and the twin-screw speed was 500 r / min. Metallic-effect flow-color masterbatch was prepared by melt extrusion and granulation.
[0073] (3) Preparation of metal effect spray-free ABS material
[0074] The metallic effect rhyolite masterbatch prepared in step (2) and the natural color ABS material prepared in step (1) are mechanically mixed uniformly at an addition ratio of 10 wt.%, thereby obtaining a metallic effect spray-free ABS material.
[0075] The prepared metal-effect spray-free ABS material was injection molded into a plate, and the flow marks and weld line colors of the metal plate were observed.
[0076] (4) Preparation of flow effect masterbatch with similar color to flow marks and weld lines
[0077] Based on the formula of the metallic effect flow color masterbatch in step (2), by removing the metallic color powder and adjusting the color of the color powder, a flow effect masterbatch with a color similar to that of the flow mark and weld line is obtained. Specifically, it is prepared from the following raw materials in parts by weight:
[0078]
[0079] The specific preparation method is the same as the method for preparing metal flow effect masterbatch.
[0080] (5) The flow effect masterbatch prepared in step (4) having a color close to the flow marks and weld lines of the metal plate is mechanically mixed with the metal effect spray-free ABS material prepared in step (3) at an addition ratio of 1 wt.%, thereby obtaining a low-defect metal appearance spray-free ABS material.
[0081] Among them, the polyacrylonitrile-butadiene-styrene copolymer (ABS) has a polybutadiene content of 20%, and the melt index tested at 220°C*10kg is 30g / 10min. The compatibilizer is ethylene-ethyl acrylate grafted maleic anhydride. The polyethylene terephthalate resin (PET) has a characteristic viscosity of 0.8dl / g. Antioxidant 1# is antioxidant 1010. Antioxidant 2# is antioxidant 168. The lubricant is ethylene bisstearamide. The weathering agent is UV-P. The metal color powder is made of aluminum, and its particle size is as large as 10um. Color powder 1# is a conventional pigment compound, which is titanium dioxide, titanium yellow, and iron red. The mass ratio is 1:0.1:0.1; color powder 2# is a conventional pigment compound, which is carbon black, titanium dioxide, titanium yellow, and iron red, and the mass ratio is 2:0.5:0.1:0.05;
[0082] Example 3
[0083] This embodiment provides a method for preparing a low-defect, metallic-looking, spray-free ABS material and its preparation method. The preparation process includes the following steps:
[0084] (1) Preparation of metal effect spray-free PC / ABS materials
[0085]
[0086] Polyacrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate resin (PC), compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, metallic toner, and toner #1 were mixed uniformly by weight and added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 210°C, 220°C, 230°C, 240°C, and 250°C, respectively, and the twin-screw speed was 500 r / min. A PC / ABS metallic-effect, spray-free material was prepared by melt extrusion and granulation.
[0087] The PC / ABS metal-effect spray-free material prepared in step (1) was injection molded into a plate, and the flow marks and weld line colors of the metal plate were observed.
[0088] (2) Preparation of flow effect masterbatch with similar color to flow marks and weld lines
[0089]
[0090] Polyethylene terephthalate resin (PET), compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, and color powder #2 were mixed by weight and then added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 210°C, 220°C, 230°C, 240°C, and 250°C, respectively, and the twin-screw speed was 500 r / min. A flow-marking masterbatch with a color similar to that of flow marks and weld lines was prepared through melt extrusion and granulation.
[0091] (3) The flow effect masterbatch having a color similar to that of the flow marks and weld lines prepared in step (2) is mechanically mixed with the PC / ABS metal effect spray-free material at a mass fraction of 1%, thereby obtaining a low-defect metal appearance spray-free PC / ABS material.
[0092] Among them, the polyacrylonitrile-butadiene-styrene copolymer (ABS) has a polybutadiene content of 20%, and a melt index of 30g / 10min tested at 220°C*10kg; the polycarbonate resin (PC) has a melt index of 20g / 10min tested at 300°C*1.2kg; the compatibilizer is ethylene-ethyl acrylate grafted maleic anhydride; the polyethylene terephthalate resin (PET) has an intrinsic viscosity of 0.8dl / g; the antioxidant 1# is antioxidant 1010; the antioxidant 2# is antioxidant 168; the lubricant is pentaerythritol tetrastearate; the weathering agent is UV-P; the metallic color powder is made of aluminum, and its particle size is as large as 10um; the color powder 1# is a conventional pigment compound, and its mass ratio of titanium dioxide, titanium yellow, and iron red is 1:0.1:0.1. Color powder 2# is a conventional pigment compound with a mass ratio of 2:0.5:0.1:0.05.
[0093] Example 4
[0094] This embodiment provides a method for preparing a low-defect, metallic-looking, spray-free ABS material and its preparation method. The preparation process includes the following steps:
[0095] (1) Preparation of natural color PC / ABS material
[0096]
[0097] Polyacrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate resin (PC), compatibilizer, antioxidant #1, antioxidant #2, lubricant, and weathering agent were mixed by weight and then added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 210°C, 220°C, 230°C, 240°C, and 250°C, respectively, and the twin-screw speed was 500 r / min. Natural-color PC / ABS material was prepared by melt extrusion and granulation.
[0098] (2) Preparation of metallic effect rhyolite masterbatch
[0099]
[0100]
[0101] Polyethylene terephthalate resin (PET), compatibilizer, antioxidant 1#, antioxidant 2#, lubricant, weathering agent, metallic color powder, and color powder 1# were mixed in parts by weight and then added to a twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder were set at 210° C., 220° C., 230° C., 240° C., and 250° C., respectively, and the twin-screw speed was 500 r / min. Metallic effect rhytide masterbatch was prepared by melt extrusion and granulation.
[0102] (3) Preparation of PC / ABS metal effect spray-free materials
[0103] The metallic effect rhyolite masterbatch prepared in step (2) and the natural color PC / ABS material prepared in step (1) are mechanically mixed at an addition ratio of 10 wt.% to obtain a metallic effect spray-free PC / ABS material.
[0104] The prepared PC / ABS metal-effect spray-free material was injection molded into a plate, and the flow marks and weld line colors of the metal plate were observed.
[0105] (4) Preparation of flow effect masterbatch with similar color to flow marks and weld lines
[0106] Based on the formula of the metallic effect flow effect masterbatch in step (2), by removing the metallic toner and adjusting the toner color, a flow effect masterbatch with a color similar to that of the flow marks and weld lines is obtained. The specific preparation method is the same as the method for preparing the metallic flow effect masterbatch, and the composition and weight proportions of the raw materials are as follows:
[0107]
[0108] (5) The flow effect masterbatch prepared in step (4) having a color close to the flow marks and weld lines of the metal plate is mechanically mixed with the metal effect spray-free PC / ABS material prepared in step (3) at a ratio of 1 wt.%, thereby obtaining a low-defect metal appearance spray-free PC / ABS material.
[0109] The polyacrylonitrile-butadiene-styrene copolymer (ABS) has a polybutadiene content of 20% and a melt index of 30 g / 10 min at 220°C and 10 kg; the polycarbonate resin (PC) has a melt index of 20 g / 10 min at 300°C and 1.2 kg; the compatibilizer is ethylene-ethyl acrylate grafted maleic anhydride; and the polyethylene terephthalate resin (PET) has an intrinsic viscosity of 0.8 dl. / g; antioxidant 1# is antioxidant 1010; antioxidant 2# is antioxidant 168; lubricant is pentaerythritol tetrastearate; weathering agent is UV-P; metallic color powder is made of aluminum, and its particle size is as large as 10um; color powder 1# is a conventional pigment compound, which is titanium dioxide, titanium yellow, and iron red, and its mass ratio is 1:0.1:0.1; color powder 2# is a conventional pigment compound, which is carbon black, titanium dioxide, titanium yellow, and iron red, and its mass ratio is 2:0.5:0.1:0.05.
[0110] Example 5
[0111] This embodiment provides a method for preparing a low-defect, metallic-looking, spray-free, flame-retardant PC material and its preparation method. The preparation process includes the following steps:
[0112] (1) Preparation of metal effect spray-free PC materials
[0113]
[0114] The flame retardant masterbatch material includes: 100 parts polycarbonate resin (PC); 25 parts flame retardant; 0.1 parts antioxidant 1#; 0.1 parts antioxidant 2#; and 0.3 parts lubricant. After mixing, the mixture is added to a twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are set at 230°C, 240°C, 250°C, 260°C, and 270°C, respectively, and the twin-screw speed is 500 r / min. The flame retardant masterbatch is prepared by melt extrusion and granulation.
[0115] Polycarbonate resin (PC), flame retardant masterbatch, compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, metallic toner, and toner #1 were mixed uniformly by weight and added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 230°C, 240°C, 250°C, 260°C, and 270°C, respectively, and the twin-screw speed was 500 r / min. A flame-retardant PC metallic-effect, spray-free material was prepared by melt extrusion and granulation.
[0116] The flame-retardant PC metal-effect spray-free material prepared in step (1) was injection-molded to form a plate, and the flow marks and weld line colors of the metal plate were observed.
[0117] (2) Preparation of flow effect masterbatch with similar color to flow marks and weld lines
[0118]
[0119]
[0120] Polyethylene terephthalate resin (PET), compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, and color powder #2 were mixed by weight and then added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 210°C, 220°C, 230°C, 240°C, and 250°C, respectively, and the twin-screw speed was 500 r / min. A flow-marking masterbatch with a color similar to that of flow marks and weld lines was prepared through melt extrusion and granulation.
[0121] (3) The flow effect masterbatch having a color similar to that of the flow marks and weld lines prepared in step (2) is added at a ratio of 1 wt.% and mechanically mixed with the flame-retardant PC metal effect spray-free material to obtain a low-defect metal appearance spray-free PC material.
[0122] The polycarbonate resin (PC) has a melt index of 20 g / 10 min at 300°C / 1.2 kg. The compatibilizer is ethylene-ethyl acrylate grafted maleic anhydride. The polyethylene terephthalate resin (PET) has an intrinsic viscosity of 0.8 dl / g. Antioxidant #1 is Antioxidant 1010, Antioxidant #2 is Antioxidant 168, Pentaerythritol tetrastearate is the lubricant, Triphenyl phosphate is the flame retardant, and UV-P is the weathering agent. The metallic toner is aluminum with a particle size of 10 μm. Toner #1 is a conventional pigment blend of titanium dioxide, titanium yellow, and iron oxide red in a mass ratio of 1:0.1:0.1. Toner #2 is a conventional pigment blend of carbon black, titanium dioxide, titanium yellow, and iron oxide red in a mass ratio of 2:0.5:0.1:0.05.
[0123] Example 6
[0124] This embodiment provides a method for preparing a low-defect, metallic-looking, spray-free, flame-retardant PC material and its preparation method. The preparation process includes the following steps:
[0125] (1) Preparation of natural color flame retardant PC materials
[0126]
[0127] The flame retardant masterbatch material includes: 100 parts polycarbonate resin (PC); 25 parts flame retardant; 0.1 parts antioxidant 1#; 0.1 parts antioxidant 2#; and 0.3 parts lubricant. After mixing, the mixture is added to a twin-screw extruder. The temperatures of zones 1 to 5 of the twin-screw extruder are set at 230°C, 240°C, 250°C, 260°C, and 270°C, respectively, and the twin-screw speed is 500 r / min. The flame retardant masterbatch is prepared by melt extrusion and granulation.
[0128] Polycarbonate resin (PC), flame retardant masterbatch, compatibilizer, antioxidant #1, antioxidant #2, lubricant, and weathering agent were mixed by weight and then added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 230°C, 240°C, 250°C, 260°C, and 270°C, respectively, and the twin-screw speed was 500 r / min. A natural-color flame-retardant PC material was prepared by melt extrusion and granulation.
[0129] (2) Preparation of metallic effect rhyolite masterbatch
[0130]
[0131] Polyethylene terephthalate resin (PET), compatibilizer, antioxidant #1, antioxidant #2, lubricant, weathering agent, metallic colorant, and colorant #1 were mixed uniformly by weight and added to a twin-screw extruder. The temperatures in zones 1 to 5 of the twin-screw extruder were set at 220°C, 230°C, 240°C, 250°C, and 260°C, respectively, and the twin-screw speed was 500 r / min. Metallic-effect rhytide masterbatch was prepared by melt extrusion and granulation.
[0132] (3) Preparation of metal effect spray-free flame-retardant PC materials
[0133] The metallic effect rhyolite masterbatch prepared in step (2) and the natural color flame retardant PC material prepared in step (1) are mechanically mixed uniformly at an addition ratio of 10 wt.% to obtain a metallic effect spray-free flame retardant PC material.
[0134] The prepared metal-effect spray-free flame-retardant PC material was injection molded into a plate, and the flow marks and weld line colors of the metal plate were observed.
[0135] (4) Preparation of flow effect masterbatch with similar color to flow marks and weld lines
[0136] Based on the formula of the metallic effect flow effect masterbatch in step (2), by removing the metallic toner and adjusting the toner color, a flow effect masterbatch with a color similar to the flow mark and weld line is obtained. The specific preparation method is the same as the method for preparing the metallic flow effect masterbatch. The composition and weight proportion of the raw materials are as follows:
[0137]
[0138]
[0139] (5) The flow effect masterbatch prepared in step (4) having a color close to the flow marks and weld lines of the metal plate is mechanically mixed with the metal effect spray-free flame-retardant PC material prepared in step (3) at an addition ratio of 1 wt.%, thereby obtaining a low-defect metal appearance effect spray-free flame-retardant PC material.
[0140] The polycarbonate resin (PC) has a melt index of 20 g / 10 min at 300°C / 1.2 kg. The compatibilizer is ethylene-ethyl acrylate grafted maleic anhydride. The polyethylene terephthalate resin (PET) has an intrinsic viscosity of 0.8 dl / g. Antioxidant #1 is Antioxidant 1010, Antioxidant #2 is Antioxidant 168, Pentaerythritol tetrastearate is the lubricant, Triphenyl phosphate is the flame retardant, and UV-P is the weathering agent. The metallic toner is aluminum with a particle size of 10 μm. Toner #1 is a conventional pigment blend of titanium dioxide, titanium yellow, and iron oxide red in a mass ratio of 1:0.1:0.1. Toner #2 is a conventional pigment blend of carbon black, titanium dioxide, titanium yellow, and iron oxide red in a mass ratio of 2:0.5:0.1:0.05.
[0141] Performance testing:
[0142] The mechanical properties of the products prepared in Examples 1-6 were tested.
[0143] Test method:
[0144] Table 1 Test conditions and test standards
[0145] Physical properties Test conditions Test standards tensile strength 50mm / min ASTM D638-14 Bending strength 3mm / min ASTM D790-17 flexural modulus 3mm / min ASTM D790-17 Melt flow rate 260℃*5kg ASTM D1238-20 IZOD notched impact strength 1 / 8" 5.5J,23℃ ASTM D256-10(2018) Heat deformation temperature 1.82MPa, 100mm span ASTM D648-18 density 23℃ ISO 1183-1:2019
[0146] The performance test results of Examples 1-6 are shown in Table 2:
[0147] Table 2
[0148]
[0149]
[0150] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiment. All technical solutions based on the concept of the present invention are within the scope of protection of the present invention. It should be noted that for those skilled in the art, various improvements and modifications that do not depart from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a spray-free material with low-defect metal appearance, characterized in that: The method comprises the following steps: S1. Inject metal-effect spray-free materials into plates and observe the flow marks and weld line colors; S2, preparing a flow effect masterbatch with a color similar to that of the flow mark and weld line; S3, mixing the flow effect masterbatch with the metal effect spray-free material to obtain the low-defect metal appearance effect spray-free material.
2. The preparation method according to claim 1, characterized in that: Include at least one of the following technical features: A1. The base material of the metal effect spray-free material is at least one of polycarbonate resin and polyacrylonitrile-butadiene-styrene copolymer; A2. The base material of the flow effect masterbatch is polyethylene terephthalate resin; A3. The amount of the rhytide effect masterbatch added to the low-defect metal appearance spray-free material is 0.5-5wt.%.
3. The preparation method according to claim 1, characterized in that: The flow effect masterbatch is prepared by mixing the following raw materials in parts by weight and then melt-extruding and granulating them:
4. The preparation method according to claim 1, characterized in that: The metal effect spray-free material is prepared by the following method S11 or method S12: Method S11 comprises the following steps: S11-1 Preparation: Wherein, polyacrylonitrile-butadiene-styrene copolymer and polycarbonate resin are not both 0; S11-2, mixing the raw materials in step S1-1 and subjecting them to melt extrusion and granulation to obtain the metal effect spray-free material; method S12, comprising the following steps: S12-1. Preparation of natural color materials The following raw materials in parts by weight are mixed and then melt-extruded and granulated to prepare the natural color material: Wherein, polyacrylonitrile-butadiene-styrene copolymer and polycarbonate resin are not both 0; S12-2, Preparation of Metallic Effect Rhythm Masterbatch: The following raw materials in parts by weight were mixed and granulated by melt extrusion to prepare a metallic effect rhyolite masterbatch: S12-3, the natural color material obtained in S12-1 and the metallic effect rhyolite masterbatch obtained in S12-2 are melt-extruded and granulated to obtain the metallic effect spray-free material.
5. The preparation method according to claim 3 or 4, characterized in that: Include at least one of the following technical features: B1, the polyacrylonitrile-butadiene-styrene copolymer, the polybutadiene content of which is 10-20%, and the melt index tested at 220°C*10kg is 20-60g / 10min; B2. The polycarbonate resin has a melt index of 10 to 60 g / 10 min when tested at 300° C. and 1.2 kg. B3, the compatibilizer is long-chain polyolefin grafted maleic anhydride or glycidyl methacrylate; B4, the intrinsic viscosity of the polyethylene terephthalate resin is 0.6 to 1.2 dl / g; B5, the antioxidant 1# is antioxidant 1010 or antioxidant 1076; B6, the antioxidant 2# is antioxidant 168 or antioxidant 300; B7, the lubricant is one or two of pentaerythritol tetrastearate, ethylene bisstearamide, and stearate; B8. The weathering agent is at least one of benzotriazole and hindered amine.
6. The preparation method according to claim 4, characterized in that: In step S12-3, the amount of the metal effect rhyolite masterbatch added to the metal effect spray-free material is 5wt.% to 50wt.%.
7. The preparation method according to claim 4, characterized in that: The flame retardant masterbatch is prepared by uniformly mixing the following raw materials in parts by weight and then melt-extruding and granulating:
8. The preparation method according to claim 7, characterized in that: The flame retardant is at least one of triphenyl phosphate, tricresyl phosphate, resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), and bisphenol A diphosphate.
9. The preparation method according to claim 4, characterized in that: The metal color powder is made of aluminum and has a particle size of 1 to 100 μm.
10. A spray-free flow effect plastic product, characterized in that: It is prepared by injection molding of a spray-free material with low-defect metal appearance obtained by the method as described in any one of claims 1 to 9.